Menantang Dominasi Hukum Patriarki: Pengalaman dan Refleksi Aktivis Perempuan dalam Mengadvokasi Implementasi UU TPKS - Asriani, Desintha Dwi; Muharomah, Defirentia One (Jurnal Perempuan, 2024)
This article describes the experiences and reflections of women activists in facing the challenges of advocating for the issue of sexual violence and the implementation of Anti Sexual Violence Law (UU TPKS) at the community level. A qualitative research method with a feminist perspective was deployed and thus data collection was conducted through interviews with women activists from different regions such as Aceh, Flores, Banjarmasin, Semarang and Yogyakarta. This study develops the perspectives of sociology of law and feminism to understand the extent to which internal and external aspects influence the implementation of the TPKS Law in the community including gender issues in it. The study results show that the implementation of UU TPKS needs to be seen as a complex and non-linear process due to the challenges of legal plurality reflected by the diversity of customary/local laws in a number of communities in Indonesia. Thus, special efforts are needed that not only focus on the provision of legal products, but also on how the legal products, such as UU TPKS, could be seen as inputs that have targets on the transformation of legal culture to the community level.